2011
DOI: 10.1254/jphs.10185sc
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Uptake in Rat Skeletal Muscle L6 Cells Is Increased by Low-Intensity Electrical Current Through the Activation of the Phosphatidylinositol-3-OH Kinase (PI-3K) / Akt Pathway

Abstract: Abstract. Activation of Akt by insulin is transmitted via phosphatidylinositol-3-OH kinase (PI-3K) and enhances glucose uptake. The PI-3K/Akt signaling is diminished in insulin resistance. Thus, approaches that activate PI-3K/Akt signaling leading to improved glucose uptake may ameliorate hyperglycemia. Here we showed that low-intensity electrical current or mild electrical stimulation (MES) activated the PI-3K/Akt signaling and increased the glucose uptake in rat skeletal muscle (L6) cells. The glucose uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…Oversupply of fatty acids accelerates beta-oxidation that increases the generation of reactive oxygen species (ROS). ROS-mediated oxidative stress activates JNK, which induces serine phosphorylation of insulin receptor substrate (IRS) that suppresses tyrosine phosphorylation of IRS by insulin, which leads to suppressed insulin-mediated PI3K and Akt phosphorylation and glucose uptake (3,17,18). Fatty acids increase proinflammatory cytokines through the toll-like receptor / JNK / NK-κB system, implying that proinflammatory cytokines could directly mediate lipid-induced insulin resistance (19).…”
Section: Discussionmentioning
confidence: 99%
“…Oversupply of fatty acids accelerates beta-oxidation that increases the generation of reactive oxygen species (ROS). ROS-mediated oxidative stress activates JNK, which induces serine phosphorylation of insulin receptor substrate (IRS) that suppresses tyrosine phosphorylation of IRS by insulin, which leads to suppressed insulin-mediated PI3K and Akt phosphorylation and glucose uptake (3,17,18). Fatty acids increase proinflammatory cytokines through the toll-like receptor / JNK / NK-κB system, implying that proinflammatory cytokines could directly mediate lipid-induced insulin resistance (19).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism of the effects of applied electrical stimulation could be the activation of signal transduction pathways, as proposed by Seegers et al (9). Indeed, studies by our group and others have demonstrated that electrical stimulation activates the PI3K-Akt pathway, resulting in the process of wound healing (10) and amelioration of hyperglycemia (11,12). We have also shown that, together with heat shock, which elevates the level of the heat shock protein Hsp72, mild electrical stimulation (MES) 2 attenuates hepatic ischemia/reperfusion injury in mice (13)(14)(15), ameliorates the diabetic phenotype and protects pancreatic ␤-cells in a diabetes mouse model (11,16), reduces inflammatory markers in healthy male subjects (17), and decreases proteinuria and renal inflammation in an Alport syndrome mouse model (18).…”
mentioning
confidence: 88%
“…To test whether electrical stimulation can activate p53, we treated HCT116 cells with electrical current at different pulse widths. Utilizing the MES conditions we employed previously (12), cells plated in 6-cm culture dishes were stimulated for 10 min with low-intensity current maintained at 6 V or ϳ1 V/cm and 55 pps at various pulse widths (0.01, 0.1, 1, or 10 ms) or in the absence of pulse (∞ ms) ( Fig. 1A and supplemental Fig.…”
Section: Mes At a Pulse Width Of 01 Ms Induces Phosphorylation Of P5mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In recent years, we have shown that MES increases HSP70 via the inhibition of protein degradation by the ubiquitin-proteasome pathway in A549 cells, 14 and that MES increases glucose uptake in the skeletal rat muscle (L6) cells. 15 Moreover, we previously reported that combination treatment with MES and HS ameliorated the diabetic phenotype in mice, 16,17 and attenuated hepatic ischemia/reperfusion injury in mice, 18 suggesting that MES and HS may have broad protective effects. However, the effect of MES and HS on articular cartilage remains unclear.…”
mentioning
confidence: 96%